Female resistance and discourses of power: Sonallah Ibrahim and Sue Monk Kidd - Abdel Hamid, Ragia Mostafa (AUC Knowledge Fountain, 2017)
This thesis is a comparative study of the relationship between knowledge and power in modern society. It provides an analysis of the different ways in which the Egyptian writer Sonallah Ibrahim and the American writer Sue Monk Kidd depict the effect of knowledge discourses on power relations in their works. Therefore, the thesis is interconnected with Michel Foucault's theory on knowledge and power and their effect on the individual in modern society. Lily and Zaat, the main female characters in The Secret Life of Bees and Zaat are both exposed to different power discourses by the social institutions in their society. Despite its focus on the two characters, the study also examines the effect of the social institutions on other female characters in the two works. In both novels, the characters attempt to challenge the effect of these discourses on their lives through different resistance mechanisms. While the characters of Sonallah Ibrahim's novel fail in countering the effects of power discourses in Egyptian society, the characters of Sue Monk Kidd's novel succeed in their resistance. The study also examines the effect of political, historical, religious and social reality on the authors' choice of their female characters' fate. Hence, the thesis becomes a study on the effects of the discourses of the power institutions in society on both the writers and their fictional characters.